Case report: Triple whammy: Synchronous radiotherapy induced glioblastoma multiforme and papillary thyroid cancer following nasopharyngeal carcinoma - Palaniandy, Kamalanathan; Kamarudin, Zalikha; Wong, Yin Ping; Mohamed Mukari, Shahizon Azura; Jiau, Winnie Xiao Hui; Bakar, Azizi Abu (Frontiers in Oncology, 2022)
Secondary malignancies following radiotherapy are well documented, with an estimated incidence of 5%. These may manifest as carcinomas, gliomas, or sarcomas within the previous radiation field. Glioblastoma multiforme following radiotherapy for nasopharyngeal carcinoma is an uncommon occurrence and carries a poor prognosis, whereas papillary thyroid carcinoma following radiotherapy is well documented, though the exact incidence is not well documented. The occurrence of synchronous radiotherapy-induced malignancy over both sites has not been described in the literature before. We describe a middle-aged gentleman diagnosed with glioblastoma multiforme and papillary thyroid carcinoma 6 years after radiotherapy for nasopharyngeal carcinoma. Though our case is the first reported case of a synchronous tumour of its nature, it is likely that such cases are under-reported. Long-term vigilance for loco-regional radiotherapy-induced secondary malignancies is a must, and the presence of a second distinct secondary malignancy must be entertained.